2013
DOI: 10.21608/ajfm.2013.19375
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Stature from Hand and Handprint Measurements among Some Egyptians Using Flatbed Scanner

Abstract: Stature is used for constructing a biological profile that assists with the identification of an individual. Currently, estimation of stature is performed from fleshed and skeletal remains. There has been little attempt to use complete or partial hand impressions left at scene of crime for estimating stature. The aim of the present study, therefore, is to assess the reliability and accuracy of using hand and handprint measurements for the estimation of stature among Egyptian. The study is conducted on 100 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In this study, sexual dimorphism was observed with higher values consistently recorded in male cases than their female counterpart in all the measured parameters for hand dimensions and handprints. This is in concordance with study conducted by a number of authors [1][2][3][4][5][6], [16][17] The most probable reason for mean values of men being higher than those of women is due to genetics [16] and their later maturity and growth cessation as seen in puberty. [1], [17] Asymmetry in bilateral handprints has been observed in few authors who reported significant statistical (p<0.05) difference between left and right handprint values in both sexes [3][4], [16], [18][19][20] which they have attributed to hand dominance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, sexual dimorphism was observed with higher values consistently recorded in male cases than their female counterpart in all the measured parameters for hand dimensions and handprints. This is in concordance with study conducted by a number of authors [1][2][3][4][5][6], [16][17] The most probable reason for mean values of men being higher than those of women is due to genetics [16] and their later maturity and growth cessation as seen in puberty. [1], [17] Asymmetry in bilateral handprints has been observed in few authors who reported significant statistical (p<0.05) difference between left and right handprint values in both sexes [3][4], [16], [18][19][20] which they have attributed to hand dominance.…”
Section: Discussionsupporting
confidence: 91%
“…Every part of the body of a person has a relationship with their height and this forms the basis of stature estimation which is one of the important parameters of identification. Estimation of stature is done by using metric method, not only in cases of mass causality such as natural disasters, accidents, massacres where body as a whole or dismembered body parts are found but also by using hand [2][3][4][5][6] and foot prints [7][8][9][10] left at the scene of crime. Numerous studies have been conducted in the past for stature estimation with positive correlation and minimum standard error of estimation using hand [11] , foot [12] , upper limb [13] , arm span [14] and lower limb [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The anatomical process includes the direct restoration of stature through calculating and adding the lengths and heights of several contiguous skeletal sections from the skull to the foot. The mathematical process uses regression formulae correlation of persons' skeletal parts to stature [4].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research work has been conducted in the past for estimating the stature form numerous body dimensions; example includes the dimensions of the head (Pelin et al 2010 ), hand (Asadujjaman et al 2019 ; Ishak et al 2012b ; Kalia et al 2008 ; Kim et al 2018 ; Krishan and Sharma 2007 ; Uhrová et al 2015 ; Zulkifly et al 2018 ), foot (Asadujjaman et al 2020a ; Hisham et al 2012 ; Kanchan et al 2008 , 2010 ; Krishan et al 2011 , 2012 ; Kuan 2018 ; Ozden et al 2005 ; Sanli et al 2005 ; Uhrová et al 2013 , 2015 ; Zeybek et al 2008 ), lower limb (Ahmed 2013a ; Nor et al 2013 ), upper limb (Ahmed 2013b ; Ismail et al 2018 ), cranium (Shrestha et al 2015 ), sternum (Yonguc et al 2015 ), lumber vertebrae (Zhang et al 2015 ), femur and tibia (Brits et al 2017 ), etc. Apart from these, handprints (Ahemad and Purkait 2011 ; Ishak et al 2012a , b ; Krishan et al 2015 ; Moorthy and Yin 2016 ; Paulis 2015 ; Salama 2013 ; Zulkifly et al 2018 ) and footprints (Abledu et al 2016 ; Asadujjaman et al 2020b ; Caplova et al 2018 ; Fawzy and Kamal 2010 ; Kanchan et al 2012 ; Khan and Nataraja Moorthy 2015 ; Krishan 2008 ; Robbins 1986 ) have already been used in various populations for estimating the stature as these are one of the commonly available clues found at the crime scene.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have been conducted for estimating the stature from footprints notwithstanding less work has performed on the handprints. In the past studies, it has been found that the handprint dimensions can be successfully used for the estimation of the stature (Ishak et al 2012b ; Krishan et al 2015 ; Moorthy and Yin 2016 ; Paulis 2015 ; Salama 2013 ; Zulkifly et al 2018 ). Those studies revealed a strong positive correlation between handprint dimensions and stature for both hands and sexes.…”
Section: Introductionmentioning
confidence: 99%